Our Kids: The American Dream in Crisis – nierówności w koncepcji kapitału społecznego Roberta P. Putnama (perspektywa edukacyjna) - Kowalski , Mirosław; Albański, Łukasz (Studia Edukacyjne, 2017)
This article examines the concept of inequality in Robert D. Putnam’s Our Kids. The article discusses the intersections of social inequality and social capital shown in the book. In particular, the issue of inequality in access to education between children from different backgrounds is outlined and critically discussed. The conclusion suggests a possible new way to look at the relationship between education and inequalities, providing a theoretical basis for educational research.